种铜铟镓硒物料的回收方法 (2018)
本发明公开种铜铟镓硒物料的回收方法，其主要包括硫酸+双氧水浸出、二氧化硫还原硒、水解分铜、碱分铟镓、置换铟、水解镓等步骤。本发明的铜铟镓硒物料的回收方法采用硫酸配合双氧水浸出，浸出率大大提高，且减少酸气污染；利用金属离子水解PH差分铜，成本低；另外，本发明采用碱性分镓，只需要调节溶液PH值，即可实现铟镓分离，分离效果好，所得到的铟、镓产品纯度较高。 A method for recycling copper indium gallium selenium materials comprises the steps of leaching by using sulfuric acid and hydrogen peroxide, reduction of selenium by using sulfur dioxide, separation of copper by using cuprous ammine complexation, alkali separation of indium and gallium, replacement of indium, hydrolysis of gallium, and the like. In the recycling method, leaching is carried out by using sulfuric acid in cooperation with hydrogen peroxide, so that the leaching rate is greatly improved, and acid gas pollution is reduced; in addition, copper is separated by using cuprous ammine complexation, deposition is not generated, metal ions can be well separated;and in another aspect, in the method, alkali separation of gallium is carried out, separation between indium and gallium can be implemented by merely adjusting the PH of a s